Learning management system‐integrated spreadsheet exercises for facility location modeling. (22nd July 2021) - Strakos, Joshua K.; Brazhkin, Vitaly
Abstract: Supply chain management students are introduced to a variety of modeling concepts. Yet learning facility location and capacity allocation modeling to the level of application and mastery proves difficult for the typical undergraduate business student. Spreadsheets facilitate the teaching of optimization modeling; however, providing feedback to students on spreadsheet assignments is an onerous and time‐consuming task for instructors. In this teaching brief, a set of learning management system (LMS)‐integrated spreadsheet exercises is presented which helps students learn spreadsheet modeling for the capacitated plant location problem. These exercises are also designed to reduce the instructor's grading burden while providing timely feedback and assessment of student performance. The effectiveness of the exercises is demonstrated by assessment data gathered from the LMS as well as postmodule student survey results.